The Polycomb proteins RING1B and EZH2 repress the tumoral pro-inflammatory function in metastasizing primary cutaneous squamous cell carcinoma. (31st January 2018) - Hernández-Ruiz, Eugenia; Toll, Agustí; García-Diez, Irene; Andrades, Evelyn; Ferrandiz-Pulido, Carla; Masferrer, Emili; Yébenes, Mireia; Jaka, Ane; Gimeno, Javier; Gimeno, Ramón; García-Patos, Vicenç; Pujol, Ramón M; et al.
Abstract : RING1B and EZH2 are members of the Polycomb family whose expression was found to be increased in metastasizing cSCC (MSCC). They repress the innate inflammatory function and promote metastases through the inhibition of the NF-κB signaling pathway. Abstract: Cutaneous squamous cell carcinoma (cSCC) is the second most common malignancy in humans and approximately 5% metastasize, usually to regional lymph nodes. Epigenetic regulation of gene expression may allow tumoral cells to acquire new functions in order to escape from the primary tumor. The aim of this study was to investigate the expression and function of proteins of the Polycomb family of epigenetic regulators in the metastatic process of cSCC. A higher expression of RING1B and EZH2 was detected by immunohistochemistry in a series of primary cSCC tumors that metastasized (MSCCs) when compared with non-metastasizing cSCCs (non-MSCCs). Stable downregulation of RING1B and EZH2 in cSCC cells results in enhanced expression of inflammatory cytokines and activation of the NF-κB signaling pathway. Accordingly, non-MSCCs display higher levels of membranous pS176-inhibitor of NF-kB kinase, and their stroma is enriched in neutrophils and eosinophils when compared with MSCCs. In vitro, hematopoietic cells exhibit a substantial migratory response to supernatants from Polycomb-depleted cSCC cells. Altogether, these data indicate that RING1B and EZH2 repress the innate inflammatory cSCC function and impair tumor immunosurveillance and suggest that patients with high-risk cSCCs could benefit from clinical therapies addressed to harness the immune response.